Mood Responses Associated With COVID-19 Restrictions - Terry, Peter C.; Parsons-Smith, Renée L.; Terry, Victoria R. (Frontiers in Psychology, 2020)
The COVID–19 pandemic resulted in more than half the world’s population being placed in lockdown to stem the spread of the virus. The severe restrictions imposed in many nations had the potential to significantly influence the physical and psychological well-being of those affected. The aim of the current study was to investigate mood responses during the period of restrictions from March–June, 2020. Mood responses of 1,062 participants (386 male, 676 female) were collected using the Brunel Mood Scale (BRUMS; Terry et al., 1999, 2003a) hosted on the In The Mood website. The mean pattern of mood responses reflected an inverse iceberg profile (Parsons-Smith et al., 2017), characterized by significantly elevated scores for tension, depression, anger, fatigue, and confusion, and below average scores for vigor; a profile associated with increased risk of mental health issues. Females reported more negative mood scores than males. Participants in the ≤ 25 age group reported the most negative profiles whereas those in the ≥ 56 age group reported the least negative profiles. Mood differences related to education status were also evident. Finally, mood scores fluctuated over time, with profiles being most negative during April and June. Overall, results confirmed significant mood disturbance during the period of COVID–19 restrictions, representing increased risk of psychopathology.